Conceptual design of a Ca–Cu chemical looping process for hydrogen production in integrated steelworks. (20th April 2017) - Fernández, J.R.; Martínez, I.; Abanades, J.C.; Romano, M.C.
Abstract: A novel configuration of the Ca–Cu looping process is proposed for the production of a H2 -enriched fuel gas by means of the sorption enhanced water gas shift (SEWGS) of blast furnace gas (BFG) in steel mills. CO2 is simultaneously removed from the gas using a CaO-based sorbent. A Cu/CuO chemical loop supplies the energy required for the regeneration of the sorbent via the exothermic reduction of CuO with coke oven gas (GOG). The process is carried out in an arrangement of interconnected fluidized-bed reactors operating at atmospheric pressure, which allows for a solids' segregation step to be introduced that will reduce significantly the solid circulation between reactors A reference case study is presented, where the SEWGS is operated at 600 °C and the regeneration of the sorbent at 870 °C. About 27% of the BFG can be decarbonized in the SEWGS reactor producing 110 Nm 3 of H2 per tonne of steel. A CO2 capture ratio of 31% with respect to the total carbon emissions in the steel mill can be achieved. More than 60% of the thermal input can be recovered as high-temperature heat, which could be efficiently recovered for producing electricity. Graphical abstract: Highlights: A novel H2 production process is proposed based on the SEWGS of blast furnace gas. A Cu/CuO chemical loop supplies the energy required for CaCO3 calcination. The system consists of three interconnected fluidized beds operating at atmospheric pressure. Possible operating windows for each stage of the process are examined. Positive results at optimal conditions show potential for further development.